2018
DOI: 10.1088/1361-648x/aadefb
|View full text |Cite
|
Sign up to set email alerts
|

Spin waves in disordered materials

Abstract: We present an efficient methodology to study spin waves in disordered materials. The approach is based on a Heisenberg model and enables calculations of magnon properties in spin systems with disorder of an arbitrary kind and concentration of impurities. Disorder effects are taken into account within two complementary approaches. Magnons in systems with substitutional (uncorrelated) disorder can be efficiently calculated within a single-site coherent potential approximation for the Heisenberg model. From the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…In metals, the life-time of the modes can be severely limited by the interaction of these collective modes with the single particle continuum, called Landau damping [14][15][16] , but means of viable engineering of longliving magnons have been proposed, such as reducing the system's dimensionality and alloying 17 . The latter method leads to a further momentum dissipation mechanism, in which the Bloch waves cease to be the eigenstates of the magnetic Heisenberg-like Hamiltonian and acquire a finite lifetime arising from the scattering on the crystal imperfections 18,19 . This picture of the weak attenuation might break down if the magnon spectra become dominated by strongly spatially localized modes.…”
Section: Introductionmentioning
confidence: 99%
“…In metals, the life-time of the modes can be severely limited by the interaction of these collective modes with the single particle continuum, called Landau damping [14][15][16] , but means of viable engineering of longliving magnons have been proposed, such as reducing the system's dimensionality and alloying 17 . The latter method leads to a further momentum dissipation mechanism, in which the Bloch waves cease to be the eigenstates of the magnetic Heisenberg-like Hamiltonian and acquire a finite lifetime arising from the scattering on the crystal imperfections 18,19 . This picture of the weak attenuation might break down if the magnon spectra become dominated by strongly spatially localized modes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a prominent debate is the study of lattice defects in low-dimensional structure by which translational invariance is broken. In particular, non-magnetic impurities can significantly alter the properties of low-dimensional magnets [23][24][25][26]. Moreover, in addition to electron-magnon interactions, i.e., Landau damping [22], and spin-orbit coupling [27], another mechanism which affects the magnon lifetime is scattering off impurities [28].…”
Section: Introductionmentioning
confidence: 99%
“…The formulation of effective-medium approaches is rather sophisticated and it leads to nontrivial numerical implementation 20,21 . Various brute-force simulations using large supercells have thus been used as alternatives which may be efficient and reliable in a number of cases, including both the spinwave spectra and values of the spin-wave stiffness 19,[21][22][23][24] . It was found that the spin stiffness of random diluted ferromagnets is reduced due to the sites without local magnetic moments as compared to the value obtained for a clean crystal with nonrandom concentration-weighted exchange interactions of the alloy.…”
Section: Introductionmentioning
confidence: 99%